Formation of the sale price in the bakery industry (Costos y Gestión, 2020)
The study aimed to identify the costs and establish the formation of the price of sale of products in a bakeryindustry located in the western region of the State of Santa Catarina. The instruments used for the datacollection were: unstructured interview, documentary analysis and direct observation. Data analysis wasperformed quantitatively by presenting data related to activity costs. The results indicated that in the bakeryindustry, homemade bread and plain cakes generate high profitability, where homemade bread showed a31% profit margin and a simple profit margin of 17%. In addition, it is concluded that the absorption costmethod indicated that homemade bread is more profitable than plain bread.
Keywords: Cost accounting; sales price formation; bakery industry